Ensuring of rehabilitation care quality provision: organizational-methodological aspect - T.M. Bezverkhniuk; I.K. Babova (Medičnì Perspektivi, 2022)
Introduction of international treatment protocols into medical care determines the need for scientific substantiation of the mechanisms of their adaptation in rehabilitation care. On the basis of a systemic approach we substantiated the organizational model of quality assurance for the provision of rehabilitation care in health care system in Ukraine, which consists of four interacting subsystems: management, functional, monitoring (resultative) and supply (process) subsystems. The state of rehabilitation care provision in Ukraine at the expense of the Social Insurance Fund of Ukraine and the National Health Service of Ukraine was analyzed. Need to renovate medical and technological documentation of rehabilitation care for the main groups of socially significant diseases that lead to disability of the population was grounded. Recommended program of rehabilitation at the health-resort stage of patients after coronavirus disease (COVID-19) is proposed for health-resort institutions as a methodical basis for the introduction of updated medical-technological standardization documents, which will contribute to improving the quality of rehabilitation care in Ukraine. Typical (recommended) rehabilitation program consists of general provisions on the organization of rehabilitation care, in particular the existing documentary base; indications, contraindications and criteria for admission to the health-resort stage of rehabilitation (in the post-acute or long-term period); diagnostic plan; regulation of actions in case of deterioration of the patient's clinical condition; approximate duration of the rehabilitation course; tasks of the rehabilitation stage; general characteristics of the resort and available natural healing resources; list of rehabilitation procedures; indicators of the effectiveness of rehabilitation care. The program was implemented in a number of health-resort institutions of Ukraine.